Twelve tips for teaching the informed consent conversation. (3rd April 2019) - Anandaiah, Asha; Rock, Laura
Abstract: Obtaining informed consent has been traditionally viewed as a mundane task, learned on the job and often relegated to an inexperienced member of the healthcare team. In reality, the process of obtaining informed consent is complex, challenging, and warrants focused teaching, observation and feedback. There are few published standards for what should be included in a high-quality informed consent conversation, and little or no guidance regarding how to best teach the process of conducting this type of shared decision-making conversation. The following twelve tips provide a roadmap for teaching the essential components of how to obtain informed consent, including both content and communication skills, with a focus on common pitfalls for trainees, and strategies to address them.